2019
DOI: 10.1111/jace.16925
|View full text |Cite
|
Sign up to set email alerts
|

A critical evaluation of indentation crack lengths in air

Abstract: An extensive overview is presented of Vickers indentation crack lengths in ceramics in air. Measurement of such crack lengths is one of the most common and powerful assessments of the fracture properties of ceramics and the overview provides a critical evaluation of observed behavior as functions of material type and indentation load, and an extensive basis for comparison of results from new materials and analyses.The overview considers single crystals, polycrystals, transforming materials, glasses, and multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 54 publications
(213 reference statements)
1
5
0
Order By: Relevance
“…where Dv env = v 0 -v env and DT env = T 0 -T env are environmental corrections that are both positive. Previous data on a range of ceramics via inert [41] and reactive [42] indentation strength measurements suggest that Dv env & 0.2v 0 and DT env & 0.5T 0 , consistent with observations [39] that show c env & 2c 0 [40]. However, the exact details of the c env /c 0 ratio are known to be dependent on test conditions (e.g., indentation load [43] and moisture content [44]).…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…where Dv env = v 0 -v env and DT env = T 0 -T env are environmental corrections that are both positive. Previous data on a range of ceramics via inert [41] and reactive [42] indentation strength measurements suggest that Dv env & 0.2v 0 and DT env & 0.5T 0 , consistent with observations [39] that show c env & 2c 0 [40]. However, the exact details of the c env /c 0 ratio are known to be dependent on test conditions (e.g., indentation load [43] and moisture content [44]).…”
Section: Discussionsupporting
confidence: 70%
“…In previous work, the dimensionless factor was found to be v 0 = 0.016(H/E) -1/2 ; the initial term in this empirical relationship was determined by averaging data for ''well-behaved'' ceramic materials [39]. For a material in air or liquid, it was later shown that the length of an indentation crack c env in a relaxed residual stress field is given by [40]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A hemispherical plastic zone of radius b surrounding a contact of surface dimension a creates the field that drives ensuing cracks of size c , depicted in Figure 1 8 . The classical relations between dimensions a and c and indenter load P for materials with well‐developed median/radial cracks have the formP/a2HP/c3/2)(Hfalse/E1/2Kc The validity of Equations and has been confirmed in a recent review by Cook 9 . A threshold condition for crack suppression may be obtained by setting a c = c c and eliminating load P from these equations:anormalcH/E)(Kcfalse/H2which differs from the BDS formalism in its dependence on the H/E term.…”
Section: Amendmentmentioning
confidence: 66%
“…Underlying the machining and wear behavior of this class of solids is the competitive interplay between plastic (or quasiplastic) deformation and brittle fracture in concentrated loading. Mechanical machining/wear is essentially a contact problem, more accurately a microcontact or nanocontact problem, fundamentally established in terms of indentation mechanics 1–9 . A principal factor in achieving acceptable surface finish is the scale of individual contacts.…”
Section: Introductionmentioning
confidence: 99%